Concepts in Architecture Between Theory and Practice - Anwar Subhi Ramdan Al-Qaraghuli (Iraqi Journal of Architecture and Planning, 2018)
Architecture on both sides, theoretical and practical, deals with many concepts, according to the intellectual visions and different trends of architecture , in general, and of architectural designer, in particular. To highlight the importance of studying the concept in the architecture in terms of theoretical and practical aspects.The research problem came to point outâ€ the lack of clear sight of the nature and levels of concepts that architecture deals with on both sides, theoretical and practicalâ€ Thus, the main goal of this research is toâ€ make a clear understanding of concepts in architecture, which identifies the nature and levels of concepts in architecture theoretically and practicallyâ€. The research methodology included the following steps: First, identifying a theoretical framework to the concepts in architecture in general, through the definition of the linguistic and conventional, and address of the specialist architectural studies, to include this framework, the four items the president are: manifestations of the concept and the level and characteristics as well as a single detection methods for concepts ,and then build the research hypothesis and testing, as I suppose Search contrast manifestations and the levels and characteristics of the concepts that deal with architecture in terms of its sides the theoretical and applied, to be then choose two levels of the samples, and included the first level (10) architectural research dealt with one concept in architecture and ensure the second level (10 ) contemporary architectural projects local and international, to test that hypothesis through comparative analysis, down to analyze the results and determine the conclusions.The research found the diversity of manifestation and the levels and characteristics of the concepts that architecture deals with in both sides theoretical (of architectural research) and practical (of architectural practice), with variation in the concentration of each sides of the manifestations and the levels and specific characteristics of these concepts. science the studies and researches provide a clear conceptual form that may give an idea to understand a specific concept and its relation to the other concepts, this studies may provides indications to identify concepts in architectural practice, and sometimes provides measurements to these concepts, while architectural practice utilizes concepts in different levels, it may adopt some subsidiary concept without the other in achieving the main concept, with achieve the overall objective of the project, even it was functional or communication between the designer as sender and receiver.